(untitled) (Bangladesh Pharmaceutical Journal, 2026)
This study comprehensively investigated Boerhavia repens (Family: Nyctaginaceae) to assess its biological potentials. Hexane (BRH), chloroform (BRC), ethyl acetate (BRE) and aqueous (BRA) fractions were obtained by fractionating the crude methanolic extract (BRX) using the modified Kupchan method. Antioxidant, anti-inflammatory and cytotoxic properties were investigated in vitro, while analgesic, anti-diarrheal and CNS depressive effects were evaluated in vivo using mouse models. BRE demonstrated significant antioxidant activity (IC50 = 1.38 μg/ml), outperforming standard BHT (1.75 μg/ml) in free radical scavenging assay and yielded total phenolic content (4.29 mg GAE/g extract), in contrast to gallic acid. Compared to standard acetylsalicylic acid (88.67% and 89.91%), BRH showed notable anti-inflammatory effects (79.64% and 61.27% inhibition) in hemolysis induced by temperature and hypotonic solution. On Vero cells, no fractions showed any signs of cytotoxicity. BRX-400 (400 mg/kg) had significant dose-dependent analgesia with a pain inhibition of 63.75% contrasting to that of standard diclofenac (66.49%) in acetic acid-induced writhing test. In the formalin test, BRX-400 exhibited greater analgesic efficacy in the chronic phase (70.41%) than in the acute phase (50.58%), while diclofenac produced 83.70% and 94.91% inhibition, respectively. Similar to diclofenac (55.67-89.0%), BRX-400 retained sustained analgesia (51.67-82.0%) in the hot plate test and showed comparable outcomes in the tail immersion test (26.18-58.86% vs 22.40-52.21%, respectively). The fractions showed no discernible antidiarrheal effect. Strong, dose-dependent CNS depression was demonstrated by the extracts; in thiopentalinduced sleep and hole-cross tests, BRX-400 presented 254.98% and 45.83–84.99% effect, respectively, comparable to standard diazepam (265.92% and 20.83-79.72%). All data were statistically significant (p<0.05). Bangladesh Pharmaceutical Journal 29(1): 81-92, 2026 (January)